Olahraga Rekreasi dan Psychological Well Being Pada Mahasiswa - Damaris Marlissa; Ade Yuni Sahruni; Dani Nurcholis (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to analyze the relationship between recreational sports and psychological well-being in college students. The study used a quantitative approach with an explanatory correlational design, conducted from September to November 2025 at university Musamus Merauke, involving 100 active students physical education, health and recreation aged 18 to 25 who participated in recreational sports at least once a week. Recreational sports were measured using a physical activity questionnaire based on the short version of the International Physical Activity Questionnaire, while psychological well-being was measured using the 42-item Ryff Psychological Well-Being Scale. Data analysis was carried out through descriptive statistics, normality tests, Pearson correlations, and simple linear regression at a significance level of 0.05. The results showed a positive and significant relationship between recreational sports and psychological well-being with a moderate strength of relationship and a contribution of 20.3 percent to the variation in students' psychological well-being. These findings indicate that the higher the student's participation in recreational sports, the higher the level of psychological well-being. This study emphasizes the importance of developing recreational sports programs in college environments as a promotive strategy to support students' mental health and psychological well-being.